Selective carbon-carbon bond activation of oxirane by a bisphosphine Pt(0) complex: a theoretical study - Pleßow, Philipp; Carbó, Jorge J.; Schäfer, Ansgar; Hofmann, Peter (Organometallics, 2015)
Platinum(0) complexes with the chelate ligand bis(di-tert-butylphosphino)methane, tBu2P-CH2-PtBu2 (dtbpm), generated in solution from appropriate precursors, are the only known transition metal species that selectively activate epoxides (oxiranes) by inserting the Pt fragment into their carbon-carbon bond. The mechanism of this unprecedented reaction is studied theoretically using the random phase approximation. We find that the reaction is kinetically controlled and is caused by the formation of a monocoordinate (dtbpm-κ1P)Pt(0) fragment rather than a (dtbpm-κ2P)Pt(0) chelate complex. Insertion into epoxide C-C bonds occurs without energy barrier. Conceivable competing reactions, oxirane C-O and C-H activation, both proceed via formation of a σ-complex, followed by small but significant barriers for insertion steps. A reversible formation of the σ-complexes would perfectly explain the observed reactivity. For an irreversible formation, we find that intramolecular rearrangement of these σ-complexes toward C-C activation products is faster than both C-O and C-H activation. In principle, the same reactivity should be expected for other monocoordinated platinum(0) phosphine complexes. However, only the specific properties of dtbpm cause the subsequent, rapid, and irreversible closing of the chelate ligand yielding stable, square-planar Pt(II) C-C activation products.